Fullerene C60 Attenuates Heart Tissue Inflammation by Modulating COX-2 and TNF-Alpha Signaling Pathways in DMBA Induced Breast Cancer in Rats - Beyaz, Seda; Aslan, Abdullah; Gok, Ozlem; Agca, Can Ali; Ozercan, Ibrahim Hanifi (Humana Press Inc, 2023)
The present study aimed to investigate the therapeutic effect of fullerene C-60 nanoparticle against heart tissue damage caused by 7,12-dimethylbenz [a] anthracene (DMBA) in female rats. Female Wistar albino rats, 8 weeks old (n = 60) weighing around (150 +/- 10 g) were used for the study. These rats were divided into 4 groups and each group included 15 rats. Groups: (i) Control Group: Fed with standard diet; (ii) C-60 Group: C-60 (1.7 mg/kg bw, oral gavage); (iii) DMBA Group: DMBA (45 mg/kg bw, oral gavage); (iv) C-60 and DMBA Group: C-60 (1.7 mg/kg bw, oral gavage) and DMBA (45 mg/kg bw, oral gavage) group. Malondialdehyde (MDA) analysis, catalase activity (CAT), and glutathione (GSH) in heart tissue were determined by spectrophotometer. In addition, heart tissue DNA damage was investigated. Caspase-3, p53, HO-1, COX-2, and TNF-alpha protein expression levels in heart tissue were determined by western blotting. As a result, Caspase-3, p53, HO-1 protein expression, GSH levels and CAT activity increased, COX-2, TNF-alpha protein expression, and MDA levels were significantly decreased in the C-60 + DMBA group compared to the DMBA group. Therefore, the fullerene C-60 nanoparticle may be a promising and effective therapy for the treatment of heart diseases associated with inflammation.
Keywords: COX-2; DMBA; Fullerene C-60; Heart tissue; p53; TNF-alpha